Comparatives Studies between Takaful Rules and Regulations in Malaysia and Indonesia: (Kajian Perbandingan antara Undang-undang Takaful di Malaysia dengan Indonesia) (Kanun: Jurnal Undang-undang Malaysia, 2019)
Asean countries have dominated the 30 percent of the global takaful (Islamic insurance) market in 2014. This development has had a major impact on the changes in takaful rules and regulations in Asean countries, especially Malaysia and Indonesia. This change is necessary to ensure that the takaful rules and regulations are always relevant to the development of the global takaful industry, and comply with Islamic law. Thus, this comparative study is aimed at analysing the similarities and differences between takaful rules and regulations through the Islamic Financial Services Act (APKI) of 2013 in Malaysia and Law No. 40 (UU40) of 2014 on Insurance in Indonesia. The findings show that there are similarities and differences in the law due to the different legal frameworks between the two countries. The results of this study are expected to contribute to legal control over takaful operators in Asean countries, especially in Malaysia and Indonesia.Keywords: Takaful Rules and Regulations, Islamic Financial Services Act (2013), Law No. 40 (2014), Malaysia, Indonesia